Pengembangan Video Pembelajaran Ekonomi SMA Berbasis Aplikasi Inshoot - Wulandari, Nur Fitri; Sofya, Rani; Ritonga, Mentari (Universitas Negeri Padang, 2024)
The development of learning media is carried out as an effort to solve student learning problems, this learning media can be used as an alternative to reduce problems in learning. This study aims to produce products in class XI economics subjects and determine the quality of the validity and practicality of the products developed so that they are suitable for use. This type of research is development research known as Research and Development (R&D), using a 4-D development model. Development of learning video media using the Inshot application on economics subjects in SMA UNP Laboratory development. This development is carried out in accordance with the development procedure that produces learning media in the form of videos. This product has gone through the validation stage, the result of media carried out by media experts are categorized as “valid”. While the validation results form two material experts, namely the final validation results from material experts were categorized as “very valid”. Furthermore, the results of the practicality test conducted by 26 students and one of the subject teacher were obtained in the “very practical’ category practicality and the results of the “very practical” teacher practicality test results.